Financing and new forms of managerialism university - Abarca Rodríguez, Allan (2012)
This article is the linkgenerated between the urgency of major universitypublic budgetary and schedule'organized anarchy', which favors the emergenceof the many common problems faced byhigher education organizations. this sponsorexploration of the scope and characteristics ofso-called "new governance schemesuniversity ", which in many countries have been developed to overcome these ambiguities.There are several reasons that certify the difficulty ofmanagerialism transfer models that are bornin different parts of the world to promote bestuniversity governments: there is a complex exercise political, economic and administrative individuals, difficulties inherent in the model 'principalagent' at the University, the joint specialinterests woven in government agencies, and the contextsdifferentiated so that universities respond to their societies.However, it is essential to discuss and venturein creating alternatives to sponsor improvementsin university bodies especially when asphyxia budget becomes an eternal dilemma